THE CORRELATION OF LEARNING STYLE AND ENGLISH ACHIEVMENT OF THE STUDENTS OF NURUL HUDA SENIOR HIGH SCHOOL - Mita Sartika; Magdad Hatim; Evi Rosmiyati (Universitas PGRI Palembang, 2023)
This study aimed to investigate the learning styles utilized by students at Nurul Huda Senior High School and their correlation with English achievement. It adopted a correlational design and employed a quantitative methodology to analyze the relationship between students' learning styles and their English performance. The study employed the VAK Model, which encompasses Visual, Auditory, and Kinesthetic learning styles. The questionnaire utilized in the research was developed based on the VAK Learning Style Questionnaire. A total of 30 tenth-grade students from Nurul Huda Senior High School participated in the study. The questionnaire results indicated that the students employed various learning styles: 20% preferred kinesthetic, 56.7% preferred visual, 23.3% preferred auditory, and others exhibited a preference for more than one learning style. Future researchers could explore different theories, employ interviews, and include a larger number of participants. Additionally, conducting similar studies at Nurul Huda Senior High School to analyze other factors influencing students' English achievement would be beneficial. The researcher hopes that by identifying students' learning styles, both students and teachers can become more aware of individual learning preferences within the classroom setting.